The power of an architect’s competences in interdisciplinary research: the case of the Belgian-Tanzanian IUC partnership (EAAE Annual Conference Proceedings, 2023)
In answer to the calls’ questions in ‘Roots of Architecture(s)’, we explain the ‘Ways of Research’ in a concrete case, with a focus on its interdisciplinary dimensions, its envisioned tangible social impact, its embedded communities’ participation and its social urgency. We identify the role of an architect’s competences in the process prior to the start of the project, and we argue that these critical, creative and collaborative problem-solving skills have been (and still are) of vital importance for its success.